Rotterdam system and irish models of consumer demand - Conniffe, D.; Hegarty, A. (Economic & Social Studies, 1980)
The form of Rotterdam (ROS) model previously applied to Irish data did not impose all the constraints on parameters suggested by Demand Theory. In this paper a method of estimating the ROS, subject to symmetry and negativity, is outlined and applied to data. The elasticity estimates obtained are compared with those obtained by O'Riordan (1976) for the Linear Expenditure Systems (LES). The substantial differences between LES estimates and "unconstrained" ROS estimates largely vanish when the ROS is subjected to full constraints. The topic of comparisons between alternative systems of demand equations is discussed.
Keywords: Rotterdam model; Demand theory